PENGARUH KECERDASAN INTELEKTUAL DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI AKADEMIK MAHASISWA MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS TADULAKO - HATIMA, KHUSNUL (Fakultas Ekonomi Universitas Tadulako, 2016)
This study determines simultaneous and partial influence of intellectual intelligence and emotional intelligence on academic achievement of Management Department Students of 2013 and 2014 at the Faculty of Economics, Tadulako University. The type of research is quantitative and sampling technique applies purposive sampling, with a total sample of 83 respondents consisting of 36 students of class 2013 and 47 students of class of 2014. Data collection methods include observation, interviews, and questionnaires. The results of this study show that the variables intelligence (X1) and emotional intelligence (X2) simultaneously influence academic achievement (Y) with sig. value of0.000 <0.05. Furthermore, variable intellectual intelligence (X1) with sig. value of 0.003, and Emotional Intelligence (X2) with sig is 0,001 that showing partial influences on academic achievement (Y).